2018
DOI: 10.1080/14767058.2018.1461313
|View full text |Cite
|
Sign up to set email alerts
|

Management of fetal growth restriction using the contraction stress test: a case-control study

Abstract: Neonatal outcomes and UA pH were slightly different between the groups managed with and without CST. However, UA pO values significantly differed between the groups. For FGR management, the use of a CST may allow for early intervention before fetal acidemia and acidosis. For establishing the effects of a CST for FGR management, analysis including several cases and investigation of long-term outcomes of newborn infants is necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…The placenta is an organ with relatively low resistance and slow blood flow. Color Doppler ultrasound can neither detect the low-speed blood flow inside the placenta villi space nor identify the individual villi blood vessels [ 13 ]. Several large cohort studies have also indicated that conventional ultrasound changes are associated with low sensitivity and specificity in the FGR population [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The placenta is an organ with relatively low resistance and slow blood flow. Color Doppler ultrasound can neither detect the low-speed blood flow inside the placenta villi space nor identify the individual villi blood vessels [ 13 ]. Several large cohort studies have also indicated that conventional ultrasound changes are associated with low sensitivity and specificity in the FGR population [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…e placenta is an organ with relatively low resistance and slow blood flow. Color Doppler ultrasound can neither detect the low-speed blood flow inside the placenta villi space nor identify the individual villi blood vessels [13].…”
Section: Discussionmentioning
confidence: 99%
“…Tanaka et al presented a case-control retrospective study about the efficacy of OCT in management of IUGR, having included 73 cases [8]. They found significant differences in oxygen saturation in the umbilical artery (UA) between the groups and concluded that OCT allows early intervention in cases of IUGR, which enables fetal acidemia and acidosis to be avoided.…”
Section: Discussionmentioning
confidence: 99%
“…Repeated spontaneous decelerations indicate imminent delivery. Contraction stress tests may allow early intervention before fetal acidemia occurs and helps in the reduction in adverse outcome [ 42 ]. We did not find any difference in FHRM monitoring, likely because we intervened before the outcome worsened.…”
Section: Discussionmentioning
confidence: 99%